2014
DOI: 10.4172/1948-5956.1000292
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Gene Mutations, their Prognostic Relevance and Molecularly Targeted Therapies in Acute Myeloid Leukemia (AML)

Abstract: Acquired genetic alterations which include balanced and unbalanced chromosome aberrations and submicroscopic gene mutations and changes in gene expression strongly influenced by pretreatment clinical features and prognosis of adults patients with acute myeloid leukemia (AML). Cytogenetic profiling separate AML patients into three broad prognostic groups: favorable, intermediate and adverse. The cytogenetic risk classifications vary to some extent for younger adult patients and for those aged 60 years or older.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 127 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…These findings suggest that these genes could be useful as prognostic biomarkers in AML, along with mutations in JAK2, cKIT, and FLT3 genes, recently proposed for their high frequency in AML (30%) and their association with a decrease in survival rate. 39 In fact, it has been suggested that large groups generated by the presence of these alterations could be divided into small subgroups, depending on the presence of less common mutations, 39 such as the ones reported in our work. These data highlight the importance of finding new biomarkers that allow a better diagnostic, prognostic, and therapy in AML.…”
Section: Discussionmentioning
confidence: 53%
“…These findings suggest that these genes could be useful as prognostic biomarkers in AML, along with mutations in JAK2, cKIT, and FLT3 genes, recently proposed for their high frequency in AML (30%) and their association with a decrease in survival rate. 39 In fact, it has been suggested that large groups generated by the presence of these alterations could be divided into small subgroups, depending on the presence of less common mutations, 39 such as the ones reported in our work. These data highlight the importance of finding new biomarkers that allow a better diagnostic, prognostic, and therapy in AML.…”
Section: Discussionmentioning
confidence: 53%